EVALUATION OF AESTHETIC SATISFACTION AND IMPORTANCE OF BODY IMAGE AMONG FEMALE UNIVERSITY STUDENTS (Fiep Bulletin - online, 2011)
The pressure imposed by society to reach the ideal body, in relation to the aesthetic standards of female makes many women start to devise a great body, which in most cases is not compatible with their biological individuality. These efforts to achieve the perfect body have been a more female than male tradition. This article aims to identify the level of satisfaction with body image and its importance among female university students and what they do to keep the aesthetics. To that end, we evaluated 210 female college students, aged between 18 and 30 years in different university courses. To collect data, we calculated the Body Mass Index (BMI), and a self-filling questionnaire, which examined the satisfaction and the attitudes held by the same measures as maintenance of aesthetics. To assess self-perception of body image, we used the set of profiles proposed by Stunkard. It has been found some women's dissatisfaction with their bodies. Most of them search leaner bodies. As to change a part of their bodies: 85% said yes and 15% answered no. About the degree of importance of aesthetics in life: 15% believe it is of fundamental importance, it is important to 82% and 3% that does not matter. As for body image be a determining factor: 55% believe it's for personal satisfaction, 22% to get a good job, 21% for lovemaking, 1% said it is not the determining factor and 1% said other. As for what they do to keep the body image: 106 female university students responded that they do physical activity, 37 go on a diet, 28 do dietary restriction and 78 do nothing.
Keywords: Body Image; Patterns; Beauticians; Personal Satisfaction